Pemanfaatan Diorama untuk Meningkatkan Pemahaman Siswa Kelas 5 SDN 060786 tentang Peran Pelaku Ekonomi sebagai Wujud Pendidik Profesional - Nakaya Hanaro Sihotang; Eva Betty Simanjuntak; Idauli Permatasari Nainggolan; Putri Febrianti Purba; Assha Uli Handayani Hasibuan (Jurnal Bintang Pendidikan Indonesia, 2025)
This study aims to enhance the understanding of fifth-grade students at SDN 060786 in the subject of Natural and Social Sciences (IPAS), specifically the topic "Economic Conditions in My Region," through the use of diorama media. The research uses the Classroom Action Research (CAR) method with the spiral model by Kemmis and McTaggart, which includes the stages of planning, action, observation, and reflection. This study was conducted in two cycles, with data collected through learning outcome tests, observations of the learning process, and interviews with the teacher to gather feedback on the use of diorama media. The results of the study show a significant improvement in both conceptual understanding and learning outcomes of the students after the implementation of diorama media. The students also demonstrated increased engagement in the learning process, becoming more active and motivated to participate in the activities. Moreover, the use of diorama media helped students understand abstract concepts more easily than through text or verbal explanations alone. These findings emphasize that the teacher’s creativity in selecting and utilizing appropriate learning media plays a crucial role in creating an interactive, meaningful, and enjoyable learning environment, ultimately improving the quality of student learning outcomes.